Effect of Magnetic Anisotropy and Particle Size Distribution on Magnetization of Antiferromagnetic Nanoparticles - Kaur, Navneet (My University, 2021)
This thesis presents structural, thermal and magnetic characterization of Ferritin and NiO nanoparticles. Ferritin is an iron storage protein present inside the body of mammals and regulates the iron overloading or deficiency. It is purchased in form of a saline suspension. Nanoparticles of NiO with average particle sizes 5 and 8 nm are prepared by heating freshly synthesized beta nickel hydroxide. The structural and morphological characterization of both samples are done by x-ray diffraction and transmission electron microscopy. Thermal decomposition of ferritin and beta nickel hydroxide is studied by thermogravimetric analyzer. The magnetization data of the samples are measured as function of temperature and applied magnetic field using a vibrating sample magnetometer. This study is found to be useful for the estimation of particle size distribution present in a superparamagnetic system.
Keywords: Magnetization; Susceptibility; Superparamagnetism; Nanoparticles; Antiferromagnetism